The Effect Of Brand Image, Product Quality, And Price On Brand Switching In Skintific Skincare In Bengkulu City - Safitri, Delfi Ayu; Damarsiwi , Eska Prima Monuque; Abi , Yudi Irawan (Jurnal Pusat Manajemen, 2025)
When a consumer buys an item, they often assess whether the item is suitable for them or not, whether it is appropriate for them or not. Therefore, consumers prioritize choosing by looking at the brand image, product quality, and price to fulfill their desires or needs when buying an item.The purpose of this study was to determine the influence of brand image, product quality, and price on brand switching of skintific skincare products in Bengkulu City. The research method used was quantitative. The data analysis methods used were multiple linear regression, determination tests, and hypothesis testing.The results of multiple linear regression have the equation Y = 8.820 + 0.209X1 + 0.732X2 + 0.278X3, because the direction of the regression is positive, it can be interpreted that if the brand image, product quality, and price increase, the brand switching of Skintific Skincare products in Bengkulu City will also increase. Brand image, product quality, and price have a significant effect on the brand switching of Skintific Skincare products in Bengkulu City, this is evidenced by a significant value of 0.000 < 0.05 meaning H0 is rejected and Ha is accepted. Product quality has a significant effect on the brand switching of Skintific Skincare products in Bengkulu City, this is with a significant value of 0.000 < 0.05 meaning H0 is rejected and Ha is accepted. Price has a significant effect on the brand switching of Wardah makeup products in Bengkulu City, this is evidenced by a significant value of 0.002 < 0.05 meaning H0 is rejected and Ha is accepted. Brand image (X1), product quality (X2), and price (X3) together have a significant influence on brand switching (Y) of Skintific Skincare products in Bengkulu City, this is proven by the F test showing a significant value of <0.000.